Inadvertent Climate Modification / Report of the Study of Man's Impact on Climate (SMIC) - Mitchell; Study Of Man'S Impact On Climate (1973)
Preface, Participants, Overview and Summary, Introduction, Major Conclusions and Recommendations, Climate and Man in Perspective, Fundamentals of Climate Change, Man's Activities Influencing Climate, The Theory of Climate, The General Theory of Climate and Climate Modeling, Effects and Impacts, Modification of the Troposphere, Modification of the Stratosphere, Units and Conversion Factors, Index.